Comment on "pathways to psychological wellbeing for patients with bladder cancer and their partners-in-care" and contextualization in the COVID-19 pandemic. (October 2020) - Caruso, Rosario; Belloni, Silvia; Albanesi, Beatrice; Piredda, Alessio; Biagioli, Valentina
Highlights: Psychological well-being of cancer patients can be jeopardized by the challenges derived from the COVID-19 pandemic. Cancer nurses are at the frontline in managing patients care between in-hospital services and home-based cancer management. Nurses could assess cancer patients' psychological need and identify pathways to improve psychological well-being to ensure continuity of care. Patients with cancer may require greater psychological support when self-isolated.